Research of Trap and Electron Density Distributions in the Interface of Polyimide/Al2O3 Nanocomposite Films Based on IDC and SAXS - 刘媛媛 殷景华 刘晓旭 孙夺 陈明华 吴忠华 苏玻 (中国物理快报：英文版, 2017)
The distributions of traps and electron density in the interfaces between polyimide （PI） matrix and Al2O3 nanoparticles are researched using the isothermal decay current and the small-angle x-ray scattering （SAXS） tests. According to the electron density distribution for quasi two-phase mixture doped by spherical nanoparticles, the electron densities in the interfaces of PI/Al2O3 nanocomposite films are evaluated. The trap level density and carrier mobility in the interface are studied. The experimental results show that the distribution and the change rate of the electron density in the three layers of interface are different, indicating different trap distributions in the interface layers. There is a maximum trap level density in the second layer, where the maximum trap level density for the nanocomposite film doped by 25 wt% is 1.054 × 10^22 eV·m^-3 at 1.324eV, resulting in the carrier mobility reducing. In addition, both the thickness and the electron density of the nanocomposite film interface increase with the addition of the doped Al2O3 contents. Through the study on the trap level distribution in the interface, it is possible to further analyze the insulation mechanism and to improve the performance of nano-dielectric materials.